2017
DOI: 10.1038/s41598-017-14731-z
|View full text |Cite
|
Sign up to set email alerts
|

Combined x-ray crystallography and computational modeling approach to investigate the Hsp90 C-terminal peptide binding to FKBP51

Abstract: FK506 binding protein of 51 kDa (FKBP51) is a heat shock protein 90 (Hsp90) co-chaperone involved in the regulation of steroid hormone receptors activity. It is known for its role in various regulatory pathways implicated in mood and stress-related disorders, cancer, obesity, Alzheimer’s disease and corticosteroid resistant asthma. It consists of two FKBP12 like active peptidyl prolyl isomerase (PPIase) domains (an active FK1 and inactive FK2 domain) and one tetratricopeptide repeat (TPR) domain that mediates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 31 publications
(57 citation statements)
references
References 71 publications
(89 reference statements)
0
57
0
Order By: Relevance
“…Human Hsp90β contains 48 isoleucine residues well spread over all domains (Supplementary Figure 2a ), including Hsp90N, the charged flexible linker (CL), which connects Hsp90N with the middle domain (Hsp90M) 37 , and Hsp90C, responsible for dimerization. FKBP51 contains two domains (termed FK1 and FK2) and three flexible TPR repeats (PDB id: 1kt0, 5njx) 64 , 65 . Previously available assignments of Hsp90 isoleucine methyl groups were confirmed and extended through site-directed mutagenesis of specific isoleucine residues in both full-length Hsp90 and isolated N–M, N, and M domains 66 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Human Hsp90β contains 48 isoleucine residues well spread over all domains (Supplementary Figure 2a ), including Hsp90N, the charged flexible linker (CL), which connects Hsp90N with the middle domain (Hsp90M) 37 , and Hsp90C, responsible for dimerization. FKBP51 contains two domains (termed FK1 and FK2) and three flexible TPR repeats (PDB id: 1kt0, 5njx) 64 , 65 . Previously available assignments of Hsp90 isoleucine methyl groups were confirmed and extended through site-directed mutagenesis of specific isoleucine residues in both full-length Hsp90 and isolated N–M, N, and M domains 66 .…”
Section: Methodsmentioning
confidence: 99%
“…Structural modeling was performed with the program Haddock 73 using both full-length human Hsp90β (PDB id: 5fwk) 19 and FKBP51 (PDB id: 1kt0, 5njx) 64 , 65 as template structures. For the final refinement steps, an additional atomic structure encompassing FK1 domain with an additional α-helix in the N-terminus (PDB id: 3o5e) was used.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously shown that interactions between the dcTPR protein FKBP51 and peptides resembling C‐terminal sequences of Hsp90 are sequence‐specific and no interaction was observed between FKBP51 and peotide containing a stretch of 10 aspartate residues . Here in this study, we systematically searched the human protein database (https://www.ncbi.nlm.nih.gov/protein/) for the protein products containing Hsp70/Hsp90‐like sequence signatures at their C terminus.…”
Section: Resultsmentioning
confidence: 99%
“…Several structural criteria can be extracted to determine the peptide motif for interaction with dcTPR domains. First, the last five amino acids in the sequence are more conserved, a notion supported by the crystallography data where they form most of the contacts within the peptidebinding groove of the dcTPR domain [2,20]. Second, conserved C-terminal aspartate or glutamate is required for binding to the dcTPR domain [3].…”
Section: Search Of Human Protein Database For the Proteins Containingmentioning
confidence: 99%